Analysis of Factors Affecting Theunderpricing of Common Shares on Initial Public Offering (IPO) In Indonesia Stock Exchange (IDX) - Novita Mandasari, Anita Wijayanti & Endang Masitoh W (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research was aimed to examine the empirical effect of theUnderwriterreputation, Financial Leverage (DER), ROA, and Earning per Share onunder pricing companies which are listed in the Indonesian Stock Exchange. Theanalysis was basedon the Underwriter Reputation, Financial Leverage (DER),ROA, and Earning per Share as independent variables and under-pricing asdependent variable. Samples of this research are companies which are listed inIndonesian Stock Exchange.Samples were taken by purposive sampling method.Documentation method was used as data collection technique.Normality test,classical assumption test, multiplied analysis linear regression, with hypothesestesting of statistic t-tests and statistic f-test were used as statistical methods.Theresults of statistic t-tests showed that Financial Leverage (DER) and ROA had noeffects on under-pricing while Underwriter Reputation and Earning per Share wereaffecting under pricing.Keywords: [Under-pricing, Under-writer, DER, ROA, EPS]